PENGARUH KEGUNAAN, KEMUDAHAN DAN KENYAMANAN TEKNOLOGI INFORMASI TERHADAP PENERIMAAN TEKNOLOGI INFORMASI (STUDI PADA BIRO UMUM SEKRETARIAT PROVINSI SULAWESI TENGGARA) - Wahyuni, Yaumi Zyaqhidah (JURNAL AKUNTANSI, 2016)
This research aimed of presented to examine the effect of Usefulnes, Easy of Uses, and Enjoyment to Technology Acceptance in bureau of the public southeast sulawesi secretariat. The data used is the qualitative and quantitative data as well as data source in this research are primary and secondary data. Multiple Linear Regression using as an approach to analyze data. The results of this research indicate that usefulness of information technology gave significant effect partially toward Acceptance of information technology, easy of uses didn’t significantly affect partially toward information technology acceptance, enjoyment didn’t significantly affect partially toward Acceptance of information technology, usefulness, easy of uses and enjoyment of easy of uses didn’t significantly affect partially toward information technology gave significant effect simultaneously toward easy of uses didn’t significantly affect partially toward Acceptance of information technology. Keywords: Technology acceptance model, Usefulness, Easy of uses, Enjoyment.